Book reviews. - Appleby, John C.; Carter, Marina; Frost, Alan; Williams, Glyndwr; Havemann, Paul; Lenman, Bruce P.; Marshall, P. J.; Rudd, Andrew; Robinson, Francis; Hall, Catherine; Ward, J. R.; Richardson, David; et al. (Journal of Imperial & Commonwealth History, 2006)
Reviews several books. "The English Atlantic in an Age of Revolution, 1640-1661," by Carla Gardina Pestana; "Creating the Creole Island: Slavery in Eighteenth-Century Mauritius," by Megan Vaughan; "Captain Cook: Explorations and Reassessments," edited by Glyndwr Williams.